Gallocatechin from Uncaria gambir Roxb as a MurB Inhibitor: A Molecular Docking Analysis and Its Therapeutic Implications: Research Article - Ilham Kurniawan (Journal of Diverse Medical Research : Medicosphere, 2026)
The rapid escalation of antimicrobial resistance demands new antibacterial strategies targeting essential and druggable bacterial enzymes. Here, we report the molecular characterization of gallocatechin, a polyphenolic compound from Uncaria gambir, as a potential inhibitor of MurB from Pseudomonas aeruginosa (PDB ID: 7ORZ), a key enzyme in peptidoglycan biosynthesis. Docking protocol validation via redocking of the co-crystallized ligand yielded high structural accuracy (RMSD = 0.991 Å). Gallocatechin exhibited a markedly enhanced binding affinity (−8.1 kcal/mol) relative to the reference ligand (−5.3 kcal/mol), corresponding to an approximately 100-fold lower predicted inhibition constant (Ki ≈ 1.09 µM vs 131 µM). Structural analysis revealed that gallocatechin establishes a dense and multi-modal interaction network, simultaneously engaging the catalytic triad (Arg166, Ser239, Glu335) through hydrogen bonding and complementary electrostatic interactions. Notably, this tri-residue engagement and dual electrostatic stabilization are rarely observed in previously reported MurB inhibitors. The binding mode supports a dual inhibitory mechanism involving both competitive substrate displacement and perturbation of the NADPH-dependent catalytic cycle. Collectively, these findings position gallocatechin as a structurally distinct and mechanistically promising scaffold for MurB inhibition, providing a rational basis for the development of next-generation antibacterial agents targeting multidrug-resistant P. aeruginosa. Further experimental validation is warranted to confirm its therapeutic potential.